1982
DOI: 10.1007/bf02662230
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids of palm oil (Elaeis guineensis)

Abstract: Mesocarp oil ofElaeis guineensis provides 1000~2000 ppm of phospholipids. Thin layer chromatography revealed that the major components are phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI) and phosphatidylglycerol (PG). Minor components are phosphatidic acid (PA), diphosphatidylglycerol (DPG) and lysophosphatidylethanolamine (LPE), and traces of lysophosphatidylcholine (LPC) and phosphatidylserine (PS) are detectable. An artifact from enzymatic transphosphatidylation in methano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 15 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…(1990), a major quantity of metal is entrapped in phosphotides during degumming. Goh et al. (1982) also reported that phosphoric acid treatment for the removal of phospholipid gums leads to the removal of substantial quantities of iron and copper.…”
Section: Resultsmentioning
confidence: 98%
“…(1990), a major quantity of metal is entrapped in phosphotides during degumming. Goh et al. (1982) also reported that phosphoric acid treatment for the removal of phospholipid gums leads to the removal of substantial quantities of iron and copper.…”
Section: Resultsmentioning
confidence: 98%
“…Goh et al [39] reported that most of the phospholipids in the palm fruit bunches remained in the aqueous by-products (55%) and the palm fibres (41%) after the oil has been mechanically extracted from the mesocarp. Phosphatidylchloline, phosphatidylethanolamine, phosphatidylinositol and phosphatidylglycerol are the main phospholipids in palm oil [39].…”
Section: Palm Oil Phospholipidsmentioning
confidence: 98%
“…About 95% of the aqueous by-products are the water fraction containing dissolved components and the remaining 5% are the fine solids and residue oil. Goh et al [39] reported that 55% of phospholipids from the palm fruit end up in the oil recovered from this aqueous stream. As the residual oil contains about 4.0% of phospholipids, this is another potential source for valorisation.…”
Section: Aqueous By-products -Phenolicsmentioning
confidence: 98%
See 1 more Smart Citation
“…phospholipids still remain in palm-pressed fiber and sludge (4). The increased production of oil palm also resulted in increased production of by-products as well as waste.…”
mentioning
confidence: 99%